PENDIDIKAN ISLAM PRESFEKTIF FILSAFAT ALJABIRI - Sukkan Arya Putra (Tarbawi, 2022)
In the context of Islamic education, Aljabiri's philosophical perspective offers a profound understanding of how to integrate Islamic values into the educational curriculum. Aljabiri's philosophy stresses the importance of a holistic approach combining knowledge with Islamic principles. Utilizing descriptive qualitative research methods, researchers gathered data through literature review and analyzed information to elucidate the concepts of Islamic education from Aljabiri's viewpoint. The findings of this study indicate that the holistic approach of Aljabiri's philosophy can help strengthen the foundation of Islam-centric education and address contemporary challenges in education. Al-Jabiri concluded that Arab revival efforts had not succeeded in formulating the development of their civilization in a proportional or scientific manner. He emphasized the significance of understanding the epistemology of Arab thought—which includes the bayani, irfani, and burhani methods as a step towards meeting the challenges of modernity through critical rationalism.